Respuesta :
Answer:
y = 3
Step-by-step explanation:
It can work well to start by eliminating parentheses.
6(y -1/3) = 4(3y -5)
6y -2 = 12y -20
18 = 6y . . . . . . . . . add 20-6y to both sides
3 = y . . . . . . . . . . . divide by 6
Answer:
y=3
Step-by-step explanation:
6(y−13)=4(3y−5)
(6)(y)+(6)(−13)=(4)(3y)+(4)(−5)(Distribute)
6y+−2=12y+−20
6y−2=12y−20
Step 2: Subtract 12y from both sides.
6y−2−12y=12y−20−12y
−6y−2=−20
Step 3: Add 2 to both sides.
−6y−2+2=−20+2
−6y=−18
Step 4: Divide both sides by -6.
−6y−6=−18−6
y=3